Effects of Check-In Check-Out on Engagement of Students Demonstrating Internalizing Behaviors in an Elementary School Setting. (February 2023) - Kladis, Kristin; Hawken, Leanne S.; O'Neill, Robert E.; Fischer, Aaron J.; Fuoco, Kristen Stokes; O'Keeffe, Breda V.; Kiuhara, Sharlene A.
Check-In Check-Out (CICO) is an evidence-based Tier 2 intervention that has most often been used to support students who exhibit externalizing problem behaviors; however, emerging research suggests that CICO may be effective when extended to students who are engaging in internalizing problem behaviors (CICO-IB). The purpose of this study was to replicate previous research using CICO to support students with internalizing behaviors as well as to extend the research using a standardized Daily Progress Report (DPR) for all students. A multiple baseline design across students was used to examine the effects of CICO-IB on social and academic engagement with four elementary students from an urban U.S. elementary school who were exhibiting internalizing behavior problems (e.g., shyness, social withdrawal). Results indicated that CICO-IB was effective in improving active academic and social engagement for all four students included in the study as measured by both teacher rating on a DPR and direct observation. Overall, the majority of teachers, parents, and students found the intervention socially acceptable. Implications for future research and practice with students who are at risk or exhibiting emotional/behavioral disorders along with limitations are discussed.